ANDROID BASED WASTE MANAGEMENT APPLICATION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Flowers used to decorate pilgrimages will be collected daily at the end of the day by transportation service providers affiliated with the company/government, as will coconuts and other items used by pilgrims, spoiled vegetables and fruits will be collected directly from farmers and market yards, and spoiled curries will be collected from homes, restaurants, and other establishments. Some of the trash will be sent to food processing facilities that create by-products, while the rest will be utilised in raw material preparation facilities or to produce biofuels and fertilisers. Beneficiaries include market yard committee members, restaurant owners, farmers, and members of the house who are responsible for maintaining pilgrimage sites